Exploring Crypto Currency through the Lens of the Sharī‘a Law: A Comparative Analysis of Scholarly Evaluations - Qadri, Hussain Mohi ud din; Malik, Fareed Ahmad; Hassan, Muhammad Mumtaz ul; Abbasi, Muhammad Azhar (Journal of Islamic Thought and Civilization, 2023)
Digital advancements and innovations have revolutionized the way we live, work, and communicate. The financial industry is one of the sectors that have been significantly impacted by digital advancements and innovations. Blockchain technology is a digital technology that has the potential to transform the financial industry. Based on blockchain, cryptocurrencies are among the most significant technological advancements of the 21st century. They have provided a new way of transacting and investing. With the rise of cryptocurrencies, there has been an ongoing debate about their compatibility with various ethical and religious beliefs. One such belief system is the Sharī‘a Law, which governs the financial practices of Muslims, worldwide. As cryptocurrencies continue to gain popularity, it is essential to understand their compatibility with the Sharī‘a Law and resolve any resulting ethical dilemmas. The fundamental issue is whether cryptocurrencies violate the principles of Sharī‘a or can be considered a permissible investment option for Muslims. The article provides a detailed overview about digital currencies. It also explores the different types of digital currencies and their underlying technologies, such as block chain and smart contracts. This research relies on a quantitative approach, utilizing a systematic review of articles By extracting and analyzing data from scholarly works, the study aims to quantify the existing discourse on the compatibility of cryptocurrencies with Sharī‘a Law. This method enables the synthesis of quantitative insights from authoritative sources, contributing to a robust understanding of the ethical implications and adherence to Sharī‘a principles in the context of cryptocurrency use.